Giant cell arteritis of the breast and breast cancer: Paraneoplastic manifestation or concomitant disease? A case report - Kafantari, E.; Sotiropoulou, M.; Sfikakis, P.; Dimitrakakis, K.; Zagouri, F.; Mandrekas, K.; Dimopoulos, S.; Dimopoulos, M.-A.; Papadimitriou, C.A. (Onkologie, 2008)
Background: Giant cell arteritis (GCA) of the breast is one of the less recognized variants of this vasculitis and may represent an isolated finding or a manifestation of a more widespread disease. Case Report: We present the case of a 74-year-old woman with malaise and a 14-day persistent fever, reaching 38°C. There was a bilateral, painless and mobile axillary lymphadenopathy and a slight tenderness over the medial and lateral upper quadrants of her left breast, as well as an independent palpable tender mass in the upper outer quadrant of the same breast measuring 2 cm in its greatest diameter. Constitutional symptoms, anemia and an elevated erythrocyte sedimentation rate suggestive of polymyalgia rheumatica were also present. An invasive ductal carcinoma of the breast with coincidental pathologic findings of GCA in the same biopsy specimen was revealed. In this case, arteritis was limited to the breast and presented with diffuse breast tenderness. No other artery was involved by GCA. All arteritis-related symptoms disappeared after the removal of the tumor. Conclusions: There is a relationship between cancer, particularly breast cancer, and GCA of the same organ, but the real nature of this association still remains unknown. Copyright © 2008 S. Karger AG.
Keywords: breast cancer; Giant cell arteritis of the breast; Invasive ductal carcinoma